2010
DOI: 10.1007/s00232-010-9297-7
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of ENaC Activity by Rosiglitazone is PPARγ-Dependent and Correlates with SGK1 Expression Increase

Abstract: Thiazolidinediones (TZDs) are peroxisome proliferator-activated receptor gamma (PPARγ) agonists used to treat type 2 diabetes. TZD treatment induces side effects such as peripheral fluid retention, often leading to discontinuation of therapy. Previous studies have shown that PPARγ activation by TZD enhances the expression or function of the epithelial sodium channel (ENaC) through different mechanisms. However, the effect of TZDs on ENaC activity is not clearly understood. Here, we show that treating Xenopus l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 53 publications
2
10
0
Order By: Relevance
“…However, the precise mechanisms underlying these effects remain controversial. We have recently shown that RGZ increases ENaC activity in Xenopus oocytes [26]. With the present data, we demonstrate that RGZ-induced stimulation of the amiloride-sensitive sodium current in mpkCCD c14 cells is serum and insulin dependent.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…However, the precise mechanisms underlying these effects remain controversial. We have recently shown that RGZ increases ENaC activity in Xenopus oocytes [26]. With the present data, we demonstrate that RGZ-induced stimulation of the amiloride-sensitive sodium current in mpkCCD c14 cells is serum and insulin dependent.…”
Section: Discussionsupporting
confidence: 59%
“…Furthermore, RXR expression has been shown in the nephron [13] in which activation of this receptor is provided by 9-cis retinoic acid, a component of FBS [30]. Therefore, it is most likely that stimulation of ENaC activity by PPARγ agonists obtained in our studies and described by other investigators [12,22,26] may in part be due to the activation of RXR by retinoic acid.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Na + reabsorption is mediated via the amiloride-sensitive epithelial sodium channel (ENaC), which exhibits high selectivity for sodium [ 15 ] and is a central requirement for Na + reabsorption across renal epithelia. ENaC expression and translocation to the plasma membrane are tightly regulated by a diverse array of hormonal [ 16 , 17 ] and physical factors [ 18 ]. Our experiments show that ROS (10 μ M) remarkably raised the membrane level of α ENaC, and thus more and more Na + flowed into the lumen, which accelerated water reabsorption and caused more serious fluid retention.…”
Section: Discussionmentioning
confidence: 99%